“Úteis a si mesmos e a pátria” : as classes de menores aprendizagens do Arsenal de Guerra de Porto Alegre/RS (1850 – 1870) - Santos, Maicon Lopes dos (2018)
The present paper is dedicated to the study of the existing political relations and interactions among work, education and welfarism at the Oficinas do Arsenal de Guerra de Porto Alegre (Porto Alegre War Arsenal Workshops) through the class of Menores Aprendizes (Underage Apprentices) between the years of 1850 and 1870. The existence of the Underage Apprentices class was a common-practice by the Imperial Army in several provinces in Brazil in the century XIX, and in this way, we try to understand how, in the case of the Rio Grande do Sul province, the admission and teaching of these destitute, orphans, exposed and indigenous within the Arsenal Workshops worked. Therefore, the main analysis involves the existence of a work and education structure organized by the Imperial State for the development of specialized and free work force, the social relations of the time in the province of São Pedro do Rio Grande do Sul and the mechanisms of survival of the poor population before the difficulties of keeping education as childhood subsistence at the time. Thus, we will show the existence of a social and political dynamics that dialogues in three biases analyzed when referring to the functioning of the institution, such as the welfarism, social control and professional formation. In this sense, we will also provide how the underage apprentices, inserted in this military context, made use of strategies and regulations imposed to them, by a superior state power, in order to also ascend within the context of the poor society in the XIX century in Porto Alegre.